The Utilization of Fermented Pig Urine as Liquid Organic Fertilizer to the Productivity of Brachiaria humudicola and Digitaria milanjiana Grass - iin melani harahap; sayed umar; nevy diana hanafi (Universitas Sumatera Utara, 2019)
The livestock farming which is unoptimilized by additional production of the livestock that they cultivaded. This research was did at Agricultural Faculty of North Sumatera University field from June to November 2017. The purpose of this research is to know the appropriate dose of fertilizer and the response of fertilizer use to productivity (plant height, production of fresh material and dry ingredients)of Brachiaria humidicola and Digitaria milanjiana grass. The research method using is Split Plot Design which is the main plot is the variety of grass (R1 = Brachiaria humidicola and R2 = Digitaria milanjiana) and as the seed plot is the fermented pig urine liquid fertilizer (P0 = control (without urine), P1 = 100 ml, P2 = 150 ml, P3 = 200 ml and P4 = 250 ml). The parameters observed were plant height, production of fresh material and dry matter production. The result show that the higher the dose of fermented pig urine liquid fertilizer so that the higher productivity produced which is using 250 ml/plots (P4) the gave increased productivity of Brachiaria humidicola and Digitaria milanjiana grass for plant height, fresh produce and production of materials dry and Digitraria milanjiana grass has a faster response in the absorption of the fermented pig urine liquid fertilizer. Keywords: Brachiaria humidicola, Digitaria milanjiana, urine pig, productivity